Towards stable molecular nanostructures on a semiconductor surface - Berner, Nina Christina (Trinity College (Dublin, Ireland). School of Physics, 2012)
The miniaturisation trend in the construction of electronic devices has recently sparked an interest in the bottom-up construction of 2-dimensional nanostructures from single organic molecular building blocks on surfaces. Covalently bonded networks are the most desirable due to their high thermal, mechanical and chemical stability. Several different reaction mechanisms have been successfully demonstrated on coinage metal substrates over the past decade. This work explores the possibility of reproducing some of these results on a more technologically relevant semiconductor surface, in particular germanium (001), using both scanning tunnelling microscopy (STM) and photoemission spectroscopy (PES) in an ultra-high vacuum environment.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin.